Epidemiological analysis of spam between brazilian states that do border with other countries, Brazil, 2015 to 2018 (Research, Society and Development, 2020)
Measles is a notifiable disease caused by an acute viral infection that occurs through contact with droplets emitted by infected people and is prevented by vaccines. The aim of this study is to carry out an epidemiological analysis of measles among Brazilian states bordering other countries. Documentary research of a quantitative nature using the statistical method. The SUS / Datasus Hospital Information System was searched as a data source, from 2015 to 2018. For the analysis of epidemiological data, Word and Excel programs were adopted as a tool, with data presented in tables. The results analyzed in the period from 2015 to 2018 show that measles hospitalizations rose from 05 to 835 in the border states, with the states of Roraima and Amazonas responsible for 94.32% of these hospitalizations and the predominant age group were under 4 years old. , with 60.72% and Pará stands out with the lowest vaccination coverage in the 4 years evaluated with 57.63%. It is concluded that the vaccination coverage of most states remained below the 95% target, showing weaknesses in the control of the disease and, as a consequence, an increase in hospitalizations, in addition to the migratory process having contributed to an imbalance in the health - disease process in these regions. This study can be improved with other studies that address the active searches made by the ESF in relation to vaccines and new vaccine strategies in the school environment.